The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1159/000008747
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted ex vivo, Normothermic Small Bowel Perfusion

Abstract: Background: In the present study, a technique for computer-assisted, normothermic, oxygenated, ex vivo, recirculating small bowel perfusion was established as a tool to investigate organ pretreatment protocols and ischemia/reperfusion phenomena. A prerequisite for the desired setup was an organ chamber for ex vivo perfusion and the use of syngeneic whole blood as perfusate. Methods: The entire small bowel was harvested from Lewis rats and perfused in an organ chamber ex vivo for at least 2 h. The temperature w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It is important to consider that this model is more advanced if compared to a classic ex vivo model which do not provide extracorporeal circulation. This model was obtained following the surgery techniques used for in vivo organ transplantations in order to preserve the organ viability and architecture during the entire experimental period [13].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…It is important to consider that this model is more advanced if compared to a classic ex vivo model which do not provide extracorporeal circulation. This model was obtained following the surgery techniques used for in vivo organ transplantations in order to preserve the organ viability and architecture during the entire experimental period [13].…”
Section: Plos Onementioning
confidence: 99%
“…It has been demonstrated that the mucosal epithelium is extremely susceptible to ischemia [11] and although ex vivo models can better reproduce the complexity of the in vivo situation when compared to in vitro models, deterioration of the explanted tissue and lack of hemodynamics can cause differences between ex vivo and in vivo data [12]. The perfusion of ex vivo tissue allow to the conservation of organ viability and structure for a longer period compared to classic ex vivo models [13]. Recent studies, showed encouraging results of swine intestinal perfused model suggesting it as a cost-effective, practical and reliable strategy for the study of intestinal physiology, pharmacology and transplantation [14].…”
Section: Introductionmentioning
confidence: 99%